Global exchange rate configurations: Do oil shocks matter? - Sascha Buetzer; Maurizio Michael Habib; Livio Stracca (European Central Bank (ECB), 2012)
Do oil shocks matter for exchange rates? This paper addresses this question based on data on real and nominal exchange rates as well as an exchange market pressure index for 44 advanced and emerging countries. We identify three structural shocks (oil supply, global demand, and oil specific demand) which raise the real oil price and analyse their effect on individual exchange rates. Contrary to the predictions of the theoretical literature, we find no evidence that exchange rates of oil exporters systematically appreciate against those of oil importers after shocks raising the real oil price. However, oil exporters experience significant appreciation pressures following an oil demand shock, which they tend to counter by accumulating foreign exchange reserves. Results for general commodity exporters are similar, showing minor differences compared with oil exporters.
Keywords: F31; Q43; 330; exchange market pressure; exchange rate; global imbalances; Oil; Structural VAR